2009
DOI: 10.1161/circulationaha.108.791384
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Therapy After Pediatric Cardiac Arrest

Abstract: Background-Hypothermia therapy improves mortality and functional outcome after cardiac arrest and birth asphyxia in adults and newborns. The effect of hypothermia therapy in infants and children with cardiac arrest is unknown. Methods and Results-A 2-year, retrospective, 5-center study was conducted, and 222 patients with cardiac arrest were identified. Seventy-nine (35.6%) of these patients met eligibility criteria for the study (age Ͼ40 weeks postconception and Ͻ18 years, cardiac arrest Ͼ3 minutes in duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 49 publications
0
94
1
10
Order By: Relevance
“…[19][20][21][22] Hypothermia has also been used following cardiac arrest to protect the brain because it reduces cerebral metabolic activity. [23][24][25][26] The clinician caring for critically ill infants and children should be aware of the potential impact of therapeutic modalities such as hypothermia on the diagnosis of brain death. Hypothermia is known to depress central nervous system function [27][28][29] and may lead to a false diagnosis of brain death.…”
Section: Prerequisites For Initiating a Clinical Brain Death Evaluatimentioning
confidence: 99%
“…[19][20][21][22] Hypothermia has also been used following cardiac arrest to protect the brain because it reduces cerebral metabolic activity. [23][24][25][26] The clinician caring for critically ill infants and children should be aware of the potential impact of therapeutic modalities such as hypothermia on the diagnosis of brain death. Hypothermia is known to depress central nervous system function [27][28][29] and may lead to a false diagnosis of brain death.…”
Section: Prerequisites For Initiating a Clinical Brain Death Evaluatimentioning
confidence: 99%
“…Patients treated with hypothermia had longer duration of cardiac arrest, more resuscitative efforts, higher lactate, and greater use of extracorporeal membrane oxygenation. After adjusting for these variables, there was no statistically significant difference in mortality between the hypothermia and standard treatment groups [169].…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 85%
“…The groundwork for this study has been well built. Three large, retrospective cohort studies that included patients from 15 hospitals affiliated with the Pediatric Emergency Care Applied Research Network have examined the outcome and identified risk factors associated with poor outcome for both in-hospital and out-of-hospital pediatric cardiac arrest [161][162][163][164][165][166][167][168][169][170][171]. Surveys from the United Kingdom and the United States have demonstrated both variability in the practice of cooling, and a widespread willingness and interest in a randomized controlled trial to study its use [172,173].…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…For children who remain in a coma after an OHCA, a TTM strategy is recommended when initiated in the ED or ICU setting. Based on the current evidence, 31,32 clinicians may target 36°C [96.8°F] to 37.5°C (99.5°F) for 5 days or may target 32°C (89.6°F) to 34°C (93.2) for 2 days followed by 3 days of normothermia. Whereas, with respect to paramedics starting TTM in the prehospital setting after pediatric cardiac arrest, there is no clear guidance on which is the correct target temperature.…”
Section: Post Arrest-pediatricsmentioning
confidence: 99%